Under the North Pole : the Wilkins-Ellsworth Submarine Expedition - Wilkins, George H. (George Hubert) , 1888-1958; Stefansson, Vilhjalmur , 1879-1962; Lake, Simon , 1866-1945; Danenhower, Sloan , 1885-; Sverdrup, Harald Ulrik , 1888-1957; Wilkins, John , 1614-1672 (Brewer, Warren & Putnam, 1931)
The history of the idea / by Vilhjalmur Stefansson -- The plans of the expedition / by Captain Sir Hubert Wilkins -- The development of the under ice submarine / by Simon Lake -- The Arctic submarine "Nautilus" / by Sloan Danenhower -- Mathematicall magick, or, The wonders that may be performed by mechanicall geometry / by I[ohn] W[ilkins]. [Facsimile reproduction of Chapter 5 of the 1648 ed.] -- Lincoln Ellsworth / by Vilhjalmur Stefansson -- Sloan Danenhower / by Vilhjalmur Stefansson -- Studies of Arctic conditions may help solve world problems / by Harald U. Sverdrup -- The endorsement of scientific groups -- Who's who on the "Nautilus" scientific staff. by Sir Hubert Wilkins. Map on lining paper.